Microcontroller Based Spectrum Analyzer - Omar H. Hamad (Al-Khwarizmi College of Engineering – University of Baghdad, 2006)
This work includes design, implementation and testing of a microcontroller based spectrum analyzer system. Both hardware and software structures are built to verify the main functions that are required by such system. Their design utilizes the permissible and available tools to achieve the main functions of the system in such a way to be modularly permitting any adaptation for a specific changing in the application environment. The analysis technique, mainly, depends on the Fourier analysis based methods of spectral analysis with the necessary required preconditioning processes. The software required for waveform analysis has been prepared. The spectrum of the waveform has been displayed, and the instrument accuracy has been checked. The basic hardware parts of the analyzer are the processor and the associated logic, storage media, communication to a central master computer and the data acquisition parts. However, the input / output structure is modular and may change according to the application requirements. The basic operating software modules, which are independent of an application, may be used as a part of a software package that can carryout other functions. A complete software development tools package to develop application programs, using IBM-PC and the analyzer instrument, are installed and realized at levels, the PC level and the analyzer instrument level.